Effects of pasture age on the genotype and phenotype of perennial ryegrass. (23rd March 2020) - Faville, Marty J.; Crush, James R.; Hong, Won; Phillips, Holly; Lee, Julia M.; Chapman, David
Abstract: Limited persistence of perennial ryegrass ( Lolium perenne L.) in dairy pastures is a significant issue in parts of New Zealand. The contribution of plant genetic background to this problem is not well understood. Temporal changes were investigated in genotypic and phenotypic composition of two perennial ryegrass cultivars (Nui SE and Alto AR37, older and newer cultivars respectively) sown as fields plots at three locations. Samples from survivor populations collected annually over 6 years from each location were established in a field nursery, analysed by simple sequence repeat (SSR) markers and assessed for vigour, leaf morphology and tiller number. SSR‐based estimates of the statistic G′ST indicated no significant ( p  > .05) genetic differentiation between survivor populations and plants grown from remnant seed (ex‐seed) after 5 years, and no significant change ( p  > .05) in within‐population genetic diversity for either cultivar at any location. SSR analysis of endophytic fungus ( Epichloë festucae var. lolii ) type revealed only limited ingress of off‐type ryegrass volunteers into plots at two locations. Vigour scores of survivor plants were not significantly ( p  > .05) different among plants collected from different locations and ex‐seed plants. Leaves on ex‐seed plants were longer ( p  < .001) than those on the survivor plants after four but not 6 years and may reflect a short‐term response to climatic conditions experienced in the field nursery. Our results suggest that the reported poor ryegrass persistence is not driven by changes in population genetic structure and that the sown cultivars survived and remained true to type.